STRATEGI PENINGKATAN PENDAPATAN MASYARAKAT HINDU PADA WILAYAH PINGGIRAN DI SIGERONGAN LOMBOK BARAT - I Nyoman Murba Widana; L. Eka M. Julianingsih P. (Institut Agama Hindu Negeri Gde Pudja Mataram, 2022)
This research is intended to conduct a study on efforts to increase the income of Hindu communities in the suburbs, especially in the Sigerongan area. This study was designed as a qualitative descriptive research to find out the strategies used to increase the income of the Hindu community. This study obtained findings in the form of strategies that can be taken to increase people's income. First, improving the quality of education is very important in order to realize an increase in welfare. Second, in order to realize an increase in welfare, it is also very necessary to pay attention to work that must be in accordance with self-competence. Third, working together is a very important activity to do in order to complete all work properly. Fourth, fostering an attitude of self-confidence is a part that is closely related to realizing the quality of work which in turn can realize an increase in welfare. Fifth, in order to realize the quality of life, it is necessary to build an attitude of self-confidence. Sixth, being grateful is one part of efforts to build a mentality to always manifest fortitude in order to create a prosperous life.